GAMBARAN KEPATUHAN DIET PADA ANGGOTA PROLANIS SELAMA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS BOJONG 2 - Moh. Khotibul Umam; Windi Imaningtias; Nurul Hidayati Listianingrum (Poltekkes Kemenkes Padang, 2021)
Non-communicable diseases (NCDs) are the leading causes of death and are responsible for the highest mortality rates in the world and in Indonesia. One of the programs for controlling NCDs especially hypertension and Diabetes at the Public Health Center (PHC) is Prolanis. One of the Prolanis programs is the monitoring of dietary adherence among Prolanis members. A descriptive research design was used as research method. The samples of this study were 34 Prolanis members in Sumurjomblang Bogo Village, the working area of Puskesmas Bojong 2. The results showed that the majority of Prolanis members in Sumurjomblang Bogo did not compliant the right schedule of diet (80%), the right type of diet (60%), and the right number of diet (60 %) for diabetes mellitus and hypertension. This may be due to lack of monitoring from health workers. Therefore, the results of this study are expected for an online diet counseling and monitoring program involving families of prolanis members during covid-19 pandemic.